ReqStore: Um Repositório de Requisitos de Projetos de Software como Apoio a Metodologia PBL - Pordeus, Paulo; Bezerra, Carla; Coutinho, Emanuel (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2015.5866, 2015)
With the growth of the Information Technology market (IT), a strong demand for different ways to develop software quality has arisen, and therefore a demand for qualified professionals. To enable these professionals, an effective teaching model is necessary for the development and improvement of skills and competencies oriented to the development of real projects with similar complexity to those found in the labor market. For this, the method of teaching Problem based Learning (PBL) has been applied in different market areas. The PBL use problems designed to initiate, motivate and focus in the acquisition of knowledge through practice, and encourage the development of skills, needed in a professional context. This study aims to develop a tool, called ReqStore, to help the teacher while using the PBL methodology with a project requirements repository. As a result of this work, we carried out an experiment in a class of Programming Fundamentals of discipline to validate tthe effectiveness of tool with use of PBL methodology.